2019
DOI: 10.1186/s13643-019-1063-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of walking speed on gait biomechanics in healthy participants: a systematic review and meta-analysis

Abstract: Background Understanding the effects of gait speed on biomechanical variables is fundamental for a proper evaluation of alterations in gait, since pathological individuals tend to walk slower than healthy controls. Therefore, the aim of the study was to perform a systematic review of the effects of gait speed on spatiotemporal parameters, joint kinematics, joint kinetics, and ground reaction forces in healthy children, young adults, and older adults. Methods A systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
167
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(226 citation statements)
references
References 74 publications
17
167
2
4
Order By: Relevance
“…Hence, the observed age-related effect on the negative work of the foot during walking might be related to the deterioration of the heel pad property with aging, but this needs to be further investigated. There has been a raising concern about the potential confounding effect of speed on the relationship between aging and gait biomechanics 14 . However, we didn't find any difference between the gait speed of the two age groups, and therefore speed was not a confounding factor to the observed gait biomechanics, and also because we didn't find any effect of age (with the exception on the negative work of the foot as discussed previously).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the observed age-related effect on the negative work of the foot during walking might be related to the deterioration of the heel pad property with aging, but this needs to be further investigated. There has been a raising concern about the potential confounding effect of speed on the relationship between aging and gait biomechanics 14 . However, we didn't find any difference between the gait speed of the two age groups, and therefore speed was not a confounding factor to the observed gait biomechanics, and also because we didn't find any effect of age (with the exception on the negative work of the foot as discussed previously).…”
Section: Discussionmentioning
confidence: 99%
“…Slower gait speed is usually associated with aging and, considering the effects of speed on gait biomechanics, variations in walking speed, within the subject or between subjects, can confound the association between a demographic predictor, such as age, and a gait biomechanics feature 14 17 . In general, maximum amplitudes of lower limb joint kinetics are directly proportional to gait speed 14 , 17 . Of note, some studies have found that young and older individuals adopt similar gait speeds, at least while walking at their self-selected pace in laboratory settings 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore suggested that the design of future training protocols should consider repeating a similar experiment on specific patient groups within a clinical setting. Third, the fixed walking speed within this study was slower than the comfortable speed range of healthy young adults (1.05–1.43 m/s) [55], but it was comparable to the reported speed used in a previous gait retraining study (0.86 ± 0.17 m/s) [10]. Finally, only one VR device was tested in this experiment, and therefore future studies should consider other models that support stereoscopic displays and position guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the aforementioned studies have shown that faster walking speed increases the level of peak and mean plantar pressures in both younger (Segal et al, 2004;Taylor, Menz & Keenan, 2004;Rosenbaum et al, 1994) and older adults (Burnfield et al, 2004) in almost all regions beneath the foot. As for younger children, a recent systematic review and meta-analysis has shown that they walk slower, compared to older ones, which lowers the cadence, step and stride length ''and decreases vertical, baking and propulsive forces'' (Fukuchi, Fukuchi & Duarte, 2019). On the other hand, younger children have smaller feet.…”
Section: Study Variablesmentioning
confidence: 99%